Impact of the spirometric definition on comorbidities in chronic obstructive pulmonary disease. (August 2021) - Meteran, Howraman; Thomsen, Simon Francis; Miller, Martin R.; Hjelmborg, Jacob; Sigsgaard, Torben; Backer, Vibeke
Abstract: Background: Little is known about how the spirometric definition of airway obstruction affects the association between COPD and comorbidities and whether these associations might be due to genetic predisposition. Aim: 1) To examine the impact of the spirometric definition on the associations between COPD and its comorbidities and 2) To examine whether these associations can be explained by shared genetic or environmental factors. Methods: 11, 458 twins, aged 40–80 years, from the Danish Twin Registry were recruited who completed a questionnaire on medical history, life style factors and had a clinical examination. COPD was defined by respiratory symptoms (RS) plus airway obstruction according to either GOLD (FR-COPD) or ERS/ATS guidelines (LLN-COPD). Self-reported physician diagnoses were used to identify comorbidities. Results: The mean age of participants was 58.4 years ±SD 9.7, mean BMI was 26.6 kg/m 2  ± SD 4.4, 52% were female and the prevalence of LLN2.5-COPD and FR-COPD was 2.5% and 6.3%, respectively. Among eight major comorbidities, multivariate logistic regression showed COPD was only associated with heart failure, whereas RS alone were associated with 6 out of 8 comorbidities after Bonferroni-correction. There was an increased risk of heart failure, ischemic heart disease, depression and pulmonary embolism in twin individuals with RS compared with the co-twin without RS. Conclusions: COPD was only associated with an increased risk of heart failure. Discordant COPD-individuals (FR-COPD+/LLN5-COPD-) were at increased risk of heart failure. Sub-analyses showed that RS, but not airway obstruction were associated with an increased risk of comorbidities. Highlights: COPD is associated with an increased risk of systemic comorbidities. This study shows that the association seems to be driven by the respiratory symptoms rather than airflow obstruction. An increased risk of having heart failure, IHD, depression and PE was observed in the twin individual with RS. Discordant COPD (fixed ratio +/lower limit of normal (5%) -) were at significant increased risk of having heart failure. This suggests that dyspnea in this group might be ascribable to underlining heart disease rather than airflow obstruction.